Pengaruh Penerapan e-SPT Terhadap Efisiensi Pemrosesan Data Perpajakan: Survey Terhadap Pengusaha Kena Pajak pada KPP Pratama X, Bandung - Ita Salsalina Lingga (Jurnal Akuntansi, 2012)
In order to improve the quality of tax services to the tax payers, the Directorate General of Taxation (DGT) implement modernization of tax administration system (e- system). This system uses e-SPT in reporting tax. By changing the system into modern system, DGT hopes that tax compliance will increase. The purpose of this research is to examine the influence on the implementation of e-SPT towards efficiency of taxation data processing. This research uses survey method with simple regression analysis. Data are collected through questionnaires which are distributed to tax payers at KPP Pratama "X" (Tax Office) in Bandung. The results of this research shows that the implementation of e-SPT has a significant influence towards efficiency of taxation data processing.